Analysis of a solarimetric database for Mexico and comparison with the CSR model. (March 2015) - Riveros-Rosas, D.; Arancibia-Bulnes, C.A.; Bonifaz, R.; Medina, M.A.; Peón, R.; Valdes, M.
Abstract: An analysis of the solar radiation database from the network of meteorological stations of the Mexican National Weather Service was carried out. The database includes global irradiance measurements from the oldest 136 stations distributed in the Mexican territory. The consistency of data acquisition from the launch of the stations until 2010 was checked, and visual inspection of graphs of daily irradiance data was carried out, for the first three years operation, to ensure quality and reliability of the data. The results indicate that less than half of the stations have an adequate regularity for data records. With a limited number of selected stations that passed the applied quality criteria, evaluation of hourly and daily global irradiations was carried out. These results were compared to satellite derived data for Mexico, based on NREL's CSR model. The results of the comparison show a good agreement between measured and modeled daily global solar irradiation with an average RMSE of 6.6%. Based on the selected stations, a daily irradiation mean of 5.5 kWh/m²/day is estimated for the country. Highlights: A solar radiation database from the Mexican National Weather Service was analyzed. Operation and calibration problems and missing data were identified. A subset of 36 stations with reliable data was selected for comparison purposes. Comparison against the CSR satellite model shows 6% RMSD on average. Bias between −7.3% and 8.8% in monthly averaged daily global irradiation.